Risk Mitigation for Cattle - Oil Palm Integration Farming (SISKA) in West Kalimantan Province - Nugraha, Aditya; Permatasari, Nia (Fakultas Pertanian Universitas Padjadjaran, 2025)
Cattle-oil palm integration (SISKA) is one strategy that can improve several achievements of the Sustainable Development Goals (SDGs) and reduce the risk of indirect land use change (ILUC). One of the problems with SISKA development is the low interest of cattle farmers in areas surrounding oil palm plantations, which is attributed to a lack of knowledge among cattle farmers regarding risk management. There have been many studies on cattle-oil palm integration systems, but research on risk mitigation has not been comprehensively analyzed. The research was carried out between February and May 2024. The population of this study consisted of the heads and members of four SISKA clusters (Meso Tani, Dekan Jaya, Rimba Makmur, and Subur Kampit) in Sanggau District, West Kalimantan Province, with a sample size of 30 individuals. This study used the House of Risk model to identify and mitigate risks. The research results showed that three of seven risk sources must be prioritized and addressed, namely, weed control using herbicides by the company, cattle entering replanting land, and inbreeding. This study resulted in three strategies for handling risk agents, namely the use of electric fences, the implementation of a rotational grazing system, and the procurement of superior bulls.